Does service quality matter in FinTech payment services? An integrated SERVQUAL and TAM approach - Vikas Sharma; Kshitiz Jangir; Munish Gupta; Ramona Rupeika-Apoga (International Journal of Information Management Data Insights, 2024)
As the number of FinTech start-ups continues to rise globally, the utilization of these services by users becomes increasingly crucial, especially considering potential risks. Various factors affect users' utilization of financial technology, with the quality of services offered by FinTech providers standing out as a significant consideration. The aim of this study is to investigate the relationship between the quality of services offered by FinTech payment platforms and the utilization of FinTech services. We develop a novel conceptual model integrating elements from SERVQUAL and TAM (the Technology Acceptance Model) to investigate these dynamics. To gain a comprehensive understanding, we employed a mixed methods research approach. This approach included a quantitative survey analyzed using a partial least squares structural equation model (PLS-SEM) to examine the proposed framework and the relationships between its constructs. Following the survey, a follow-up focus group discussion with industry experts and academics was conducted to delve deeper into the findings and explore the ''why'' behind the statistical relationships. The findings reveal a significant impact of the quality of services offered by FinTech payment service providers on the utilization of such services. It demonstrates that in the FinTech sector, perceived usefulness does not always dominate perceived ease of use. Moreover, it confirms the profound influence of perceived usefulness in shaping attitudes and subsequent behaviour related to technology use. These insights contribute to an enhanced understanding of the factors driving the utilization of FinTech services.